Multimodal-Semiotics Analysis: The Meaning of Language and Visual in the Advertisement Indomie Ramadan Edition #AmbilNikmatnya Ramadan, Bareng Indomie - Anugrah, Inayah; Adiwinata, Akbar (Journal of Language, Literature and Teaching, 2025)
This study discusses the multimodal analysis in the advertisement of Indomie Ramadan #AmbilNikmatnya Ramadan, Bareng Indomie. Advertisement has a function as a promotional channel intended to display or introduce a product to a wide audience. Advertisement in print or digital media is also a text that has complex meaning. The complexity of meaning arises because an advertisement conveys messages not only using language elements but also nonverbal components, such as visual elements. Therefore, to understand the complexity of meaning, conducting a multimodal analysis in the advertisement is very important. The multimodal analysis presented in this research uses the theory of Systemic Functional Linguistics (SFL). The multimodal analysis model was created by integrating the multimodal theory of Anstey Bull with the multimodal analysis framework of Kress and Van Leeuwen. The results of the analysis of Indomie Ramadan Edition #AmbilNikmatnya Ramadan, Bareng Indomie show that the advertisement has a multimodal semiotic system that includes linguistic, visual, and gestural components.